Prediction of aerobic and anaerobic capacity from lactate relative change during isocapnic buffering phase in elite athletes - روح الله نیکویی; محسن حسن لی (Shahid Beheshti University, 2013)
Purpose: The aim of this study was to investigate the prediction of aerobic and anaerobic capacity from lactate relative change during isocapnic buffering phase in elite athletes. Methods: eight endurance and six sprint elite cyclists participated in the present study and performed one standard incremental test and a supramaximal exercise test on a cycle ergometer until exhaustion in 2 separate sessions. During the incremental test Breath-by-breath measurement of respiratory gas was performed and during the last 30 seconds of each 3-minute stage, blood samples were collected for lactate measurement. Lactate threshold (LT) and respiratory compensatory threshold (RCT) were defined as abrupt increase in blood lactate concentration in lactate - workload and abrupt increase in CO2 respiratory equivalent. Isocapnic buffering phase was defined as the time between LT and RCT. Two independent sample t-test was used for all comparison between groups and the relationship between variables was measured by Person correlation test. Results: lactate relative changes during isocapnic buffering phase in anaerobic cyclists were significantly higher than endurance group (p<0.05). Significant correlation was found between lactate relative changes during isocapnic buffering phase and VO2max (p<0.05) and maximum accumulative oxygen deficiency (p < 0.05). Conclusion: In summery our results showed lactate relative changes during isocapnic buffering phase is different between endurance and anaerobic athletes. Also the significant correlations that found between lactate changes during this phase and aerobic and anaerobic indexes point the note that this variable could be used for prediction of aerobic and anaerobic capacity.